Drug Trafficking Wars: Enforcement Versus Smugglers and Smugglers Versus Smugglers. (April 2014) - Che, Ying; Benson, Bruce L.
Decision making in the face of risk from law enforcement is considered from the perspective provided by theoretical models of interdependent decisions of potential drug smugglers regarding entry and the use of violence following entry. Implications of three different models of decision making under risk are examined: expected value, expected utility, and prospect theory. The theoretical results help explain many observed characteristics of drug-smuggling operations and allow clarification of some implications drawn from studies of smuggling behavior that were not considered in the context of such models.